Antecedents on Consumer Purchasing Decision: A Perspective Self Individual Factors Theory and EKB Model - Djakasaputra, Arifin; Juliana, Juliana; Tarigan, Sri Aprianti; Assaly, Arifin; Elyzabeth , Elyzabeth (AGUSPATI Research Institute, 2021)
The individual personality factors that usually affect consumers' purchasing decisions include age or life cycle stage, job, economic condition, lifestyle, personality, or self-image. The consumer's purchasing decisions related to goods depends on various factors such as brand, quality, after-sales services, warranty, advertising, rebates, offers, discount, mode of payment, display, salesperson behavior, store location, and many more. Grand Duck King Restaurant Medan has confirmed that the number of consumers has been decreasing these recent months. It has been suspected that this problem is due to consumer factors. The research objective is to determine whether individual factors affect consumers' buying decisions using the EKB model and analyze how strong the effect of individual factors is on consumers' purchasing decisions using the EKB model. The population that the writer used is the consumers at grand Duck King Cambridge Medan, which are 101 people; by using Slovin's Formula, the sample size is 81 consumers, and use the simple random sampling technique which the consumers have the same chance to be chosen as the sample. The results from the analysis are individual factors that affect consumers' purchasing decisions at Grand Duck Restaurant King Cambridge Medan, and personal characteristics have a strong and positive effect on consumers' buying decisions at Grand Duck King Restaurant Cambridge Medan. Keywords : Individual Factors and Consumer's Purchasing Decision.